Potencial bioativo dos resíduos de sapoti (Manilkara zapota (L.) P. Royen) e elaboração de bebidas fermentadas da polpa de sapoti - Aquino, Tracy Anne Cruz (2020)
Sapodilla (Manilkara zapota (L.) P. Royen) is an exotic fruit, native from southern Mexico and Central America, adapted to tropical countries and the northeastern of Brazil has showed excellent conditions for its development and production. Over the years, the development of new products as an alternative for the use of fruits, as well as the extraction of compounds of industrial interest in pulp and waste extracts has been studied. Thus, this work aimed to evaluate the bioactive potential of sapodilla peel and seed extracts obtained by maceration and ultrasound and elaborate and characterize the volatile profile of different fermented beverage formulations using sapodilla pulp. Initially, perform a physical-chemical analysis of the pulp and sapodilla residues. Then, extracts of peel and seeds in acetone, methanol and ethanol, between 40 and 80% were selected and determined the contents of complete phenolic compounds, total flavonoids and antioxidant activity. Bioactive compounds were used and quantified in waste extracts by high-performance liquid chromatography. A sapoti pulp was used in different formulations of fermented beverages and compounds of alcoholic beverages used and quantified by gas chromatography coupled to the mass spectrometer. The highest levels of phenolic compounds were obtained in 50% methanol peel extract by maceration (234.32 mg EAG/100g of residue) and in 80% methanol seed extract by ultrasound (65.28 mg EAG/100g of residue), also demonstrate higher antioxidant activity. Regarding the total flavonoids, the highest levels were in the peel extract in 80% ethanol by ultrasound (90.85 mg QCE/100g) and in the seed extract in 80% ethanol by maceration (50.39 mg QCE/100g), which showed higher antioxidant activity in ABTS among the extracts obtained by macerating 664.4 μM of Trolox/g of residue). Seven polyphenolic compounds were identified and quantified by liquid chromatography, in the analyzed extracts, gallic acid being the major compound found. In the analysis of volatile compounds in the different formulations of sapodilla fermented, 85 volatile compounds were identified, among which 3-Methyl-1-butanol, 2-Phenylethanol and Ethylbenzoate had the highest levels (13007.99; 8439.79; and 4,990, 94 µg/kg, respectively). The production of these compounds was optimized by the response surface methodology where maximum productions of 3-methyl-1-butanol were obtained for soluble solids content greater than 18.5 °Brix, for Ethylbenzoate inoculum concentrations greater than 8.8 g/L, and for 2-phenylethanol soluble solids content between 12,9 and 17.8 ° Brix, and inoculum concentrations between 5.2 and 7.4 g/L. Sapodilla residues demonstrated potential as a source of bioactive compounds, and fermented beverage formulations stood out as a possible product obtained from sapodilla pulp, whose sensory characteristics are yet to be explored.